2023
DOI: 10.1021/acsnano.2c10596
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled TaOX/2H-TaS2 as a van der Waals Platform of a Multilevel Memristor Circuit Integrated with a β-Ga2O3 Transistor

Abstract: Two-dimensional (2D)-layered material tantalum disulfide (2H-TaS 2 ) is known to be a van der Waals conductor at room temperature. Here, 2D-layered TaS 2 has been partially oxidized by utraviolet-ozone (UV-O 3 ) annealing to form a 12nm-thin TaO X on conducting TaS 2 , so that the TaO X /2H-TaS 2 structure might be self-assembled. Utilizing the TaO X /2H-TaS 2 structure as a platform, each device of a β-Ga 2 O 3 channel MOSFET and a TaO X memristor has been successfully fabricated. An insulator structure of Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Memristors are emerging as future storage devices owing to their desirable structure for high-density integration and vertical stacking based on their crossbar array. 1–3 In addition, studies in recent years have reported that memristors have the potential to be used in advanced applications such as neuromorphic systems owing to their characteristics such as multi-state switching, 4,5 low-power consumption, 6,7 and non-volatility. 8,9 Despite the diverse potential of memristors, one of the biggest challenges in implementing practical applications using memristive devices is ensuring uniformity and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Memristors are emerging as future storage devices owing to their desirable structure for high-density integration and vertical stacking based on their crossbar array. 1–3 In addition, studies in recent years have reported that memristors have the potential to be used in advanced applications such as neuromorphic systems owing to their characteristics such as multi-state switching, 4,5 low-power consumption, 6,7 and non-volatility. 8,9 Despite the diverse potential of memristors, one of the biggest challenges in implementing practical applications using memristive devices is ensuring uniformity and reliability.…”
Section: Introductionmentioning
confidence: 99%